Sociodemographic characteristics and reproductive health factors associated with maternal knowledge and practice of infection prevention in neonates in North Dayi District, Ghana - Lawrence Sena Tuglo; Benjamin Adu Agyekum; Edward Delali Darku; Natabou Morine Alida; Kitso Palesa Seelo; Khauhelo Magaga; Kudzai Victor Chiambiro; Jessica Dzigbordi Tuglo; Sylvia Mawusinu Sakre; Desmond Dzidzornu Otoo; Jonathan Mawutor Gmanyami (Frontiers Media S.A., 2023)
BackgroundNeonates are at a greater risk of infection, but data on the maternal knowledge and practice of infection prevention in neonates (IPNs) are scarce. This study aimed to assess sociodemographic characteristics and reproductive health factors associated with maternal knowledge and practice of IPNs in North Dayi District, Ghana.MethodsThis was a multicenter cross-sectional study conducted among 612 mothers. A structured questionnaire was used for data collection adapted from previous studies and the IPN guidelines of the World Health Organization (WHO). Bivariable analyses were performed to determine the association between maternal knowledge and practice of IPNs and sociodemographic characteristics and reproductive health factors.ResultsAnalysis showed that less than one-fifth of the mothers (12.9%) had poor knowledge of IPNs, while 21.6% incorrectly practiced it. Mothers who had poor knowledge of IPNs [adjusted odds ratio (AOR) = 13.33 (95% CI: 7.69-23.26), p < 0.001] were more likely to have a poor practice of IPNs.ConclusionAbout one-fifth of the mothers in this study had poor knowledge or poor practice of IPNs according to the WHO's guidelines. The Health Directorate of North Dayi District should explore the risk factors associated with poor IPNs and increase successful guideline adherence with intensified educational outreach and campaigns.